IMPROVING ACCOUNTING AND AUDITING IN THE HOTEL INDUSTRY OF UZBEKISTAN - Lobarhon Asqarova; Lobarhon Asqarova (Scholar Express Journals, 2023)
This article analyzes the essence of the audit analysis of property use and performance of hotels in Uzbekistan. Indicators representing this area are also discussed.
Keywords: auditing; hotel; analyze; hotel's property